Discussion on China's reform in gymnastics management system under state power centralizing system - DIng, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: China`s state power centralizing system has contributed to the success of Chinese gymnastics team rankings in the world gymnastics competitions in recent years. But due to the improper management system of gymnastics, China is facing a series of problems such as shortage of Chinese gymnasts and difficulties for gymnasts` employment after retiring from gymnastics training. So it is a necessary reform to overcome the present Chinese management system of gymnastics, so that a sustainable development Chinese gymnastics occurs. Methods To conduct field survey to civic, provincial and national gymnastics teams that represent Chinese management system of gymnastics and visit related coaches, gymnasts and administrators; to interview by phone and investigate gymnastics clubs, collegiate gymnastics teams and national teams in western advanced countries. Result Although Chinese gymnasts won excellent achievements in ceremonial world gymnastics competitions because of the advantage of state power centralizing system, however, the faults of lower gymnasts` academic levels, difficulties after gymnasts` retirement, gymnasts` shortage, over-dependence on governments in finance resulting from present Chinese management system of gymnastics make us realize the imminence and necessity to reform it. Discussion The successful experiences from the gymnastics development of western advanced countries compensate for the shortcoming in Chinese present management system. We can learn from their measures of gymnastics development to apply the running mode of commercialization and general adoption of the market principle properly. According to Chinese actual situation, we should try to build gymnastics clubs as the organizing style in the economic advanced districts; change the situation of possessing artistic gymnastics only without recreational gymnastics in China and make out the related teaching contents, styles and competition systems; take full advantage of sports, entertainment media and official websites of gymnastics to intensify the propaganda; stipulate for the preferential policies to encourage more parents to send their children for gymnastics training for making sure the continuity of talented gymnasts on different levels. Meanwhile, we need to accelerate the enhancement of present gymnasts` academic levels and provide the retired gymnasts with more positions with the combination of sports and education. Through the reform on the shortcomings of Chinese management system of gymnastics under the state power centralizing system, it is beneficial to the sustainable development of the cause of Chinese gymnastics and shae situation of both government and society participation in the construction and development of Chinese gymnastics, so that China will follow the direction of virtuous circle to develop its cause of gymnastics continuously.